Current antiviral agents against human adenoviruses associated with respiratory infections - Li, Lexi; Xie, Zhengde; Xu, Lili (Frontiers in Pediatrics, 2024)
Human adenoviruses (HAdVs) are important pathogens responsible for respiratory infections. In children and immunocompromised patients, respiratory infections can cause considerable morbidity and mortality. Currently, there are no approved effective and safe antiviral therapeutics for the clinical treatment of HAdV infections, even those that have undergone preclinical/clinical trials. However, many compounds and molecules with anti-HAdV activity have been explored, and some candidates are undergoing clinical development. Here, we reviewed the reported in vitro and in vivo efficacies, as well as the therapeutic potential of these antiviral compounds, providing an overview and a summary of the current status of anti-HAdV drug development.